Knowledge as "quality non-conformance": A critical case study of ISO 9000 and adult education in the workplace. - Fred M. Schied; Vicki K. Carter; Judith A. Preston; Sharon L. Howell (Adult Education Research Conference, 1997)
The study focused on the impact of the process seeking ISO 9000 registration and the way in which learning processes come to be defined as defective.